The Relationship of Self-Efficacy for and Enjoyment of Learning Chinese as a Foreign Language With Chinese Academic Achievement of Grades 7 and 8 Students at Pramandanijianukroah School, Bangkok, Thailand - Li, Zheng; González González, Orlando Rafael (Scholar: Human Sciences, 2021)
The main purpose of this study was to determine if there was a significant relationship of self-efficacy for and enjoyment of learning Chinese as a foreign language with Chinese academic achievement of Grades 7 and 8 students at Pramandanijianukroah School, Bangkok, Thailand. A total of 126 students from Grade 7 and 139 students from Grade 8, enrolled during the academic year 2019-2020, participated in this study. The Questionnaire of Chinese Self-Efficacy was used to measure participants’ self-efficacy for learning Chinese as a foreign language, while the Questionnaire of Chinese Language Enjoyment was used to measure participants’ enjoyment of learning Chinese as a foreign language. The Grade 7 and Grade 8 final exams of Chinese language subject for Term 1 were used to measure participants’ Chinese academic achievement. Descriptive statistics (means and standard deviations) and correlational analysis (using multiple correlation coefficient) were performed on the collected data. The findings indicated that participants’ self-efficacy for learning Chinese as a foreign language was slightly low. The level of enjoyment of learning Chinese as a foreign language was found to be neither high nor low for Grade 7 students, whereas it was high for Grade 8 students. Chinese academic achievement for Grade 7 students was found to be satisfactory, while for Grade 8 students it was good. The multiple linear relationship of self-efficacy for and enjoyment of learning Chinese as a foreign language with Chinese academic achievement was significant and strong for Grade 7 students, whereas it was significant and moderately strong for Grade 8 students.